The Edge Malaysia - The Edge Communications Sdn Bhd. (Petaling Jaya, Selangor : The Edge Communications, 2004)
Provides real-time financial news and articles from The Edge, the weekly newspaper for business and investment from 12 Jan 04 - 24 Okt 2010
Duplicate positive silver halide 35mm x 30.5m. silver microfilm roll no. 1 to no. 44(12-01-2004) to (24-10-2010)
Title from newspaper title
Keywords: Investments -- Malaysia -- Newspapers; Business -- Newspapers; Asia, Southeastern -- Economic integration